The user participation on facebook pages of the three Portuguese tv news channels – RTP3, SIC NOTÍCIAS, AND TVI24 - Ferreira, Sónia (2017)
In recent decades, the national and international media contexts, in particular television, media significantly changed. Although they were not created for the purpose, the role that social networks, in particular Facebook, have taken as a content diffusion platform is unquestionable. Nowadays, traditional media (radio, newspaper, television) use the Web’s potential to distribute news content (Canelas, 2011). Currently, all TV news channels in Portugal have a website or a page on social networks. TV stations have increased communication channels with the public on digital platforms and study strategies that promote the participation and interaction with the news content (Cazajeira, 2015). The TV / Internet convergence will not only reach the content, but also the consumer, who becomes an interactive and participative audience. This reality imposes on journalism a continuous and updated news production system, dependent on a user being permanently connected to the Internet (Cazajeira, 2015). In fact, an ERC report (2015) confirms the relevance that social media has assumed in the publication and consumption of news. Social networks are recognised as one of the most important means for news media consultation, right after television, and the practice of sharing news is very common among consumers of online news in Portugal. Furthermore, when compared to other countries analysed by Reuters Institute (Newman, Levy, & Nielsen, 2015), Portuguese consumers are those who make the most comments to online news, preferring social networks to news sites. Considering the importance of new online platforms for journalism, this study aims to present a quantitative analysis of user participation on the Facebook pages of the three Portuguese TV news channels, specifically RTP3, SIC Notícias and TVI24, between 8 and 14 February 2016. To track this participation, the following parameters were used: the "like" button as a way to study the demonstration of publication interest; "sharing" of a particular element, be it a photo, a video or a text, on their own Timeline, the Timeline of a friend or by private message. This monitoring is important to understand the dissemination of news content; and the comments area. The number of comments will help understand the dynamics and the discussion that the publication has on the public. The results of 1063 posts indicate that of the analysed parameters - "Like", "Comment", and "Share" – the one with the greatest power of participation among the users of the pages of the three Portuguese TV news channels is the "Like" system, followed by "Share" and then "Comment". Analysing the thematic that create the most user participation with "Likes" and “Comments” parameters are "Science and Technology". “Education” and “Humorous/Satirical/Unusual Finally, the publications available end of the night (10pm-1am) has better participation rates.